Can Czechia Benefit from Immigration? : Estimation Using a VAR Model - Mikušek, Vít; Frömmel, Tomáš; Slaný, Martin, 1982-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2020)
In relation to the problem of declining labour force participation rates due to population ageing, immigration policy has become one of the potential remedies discussed among developed countries. Utilizing vector autoregressive models, the thesis estimates the effects of immigration to Czechia on the two of its macroeconomic aggregates as proxies of the economic development, namely the real GDP per capita and the unemployment rate between 2006-2019 in quarterly series. According to the model and the impulse response function output, immigration has no statistically significant effect on any of these aggregates. Conversely, immigration was found to be Granger caused by both the real GDP per capita and the unemployment rate. Following a brief overview of the ‘target economic migration’ policies and the migrant structure in Czechia, the reason for the insignificance of the effect of immigration on the unemployment rate might be the complementarity of the migrant and the domestic workers, while the insignificance of the effect on the real per capita production might be caused by a similar average labour productivity.
Vedoucí práce: Tomáš Frömmel
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses